Protein-Energy Synchronization Index of Various Energy Source of Feed Concentrate for Ruminants - Afduha Nurus Syamsi; Hermawan Setyo Widodo; Harwanto Harwanto (Jurnal Agripet, 2021)
ABSTRACT. The study aimed to determine the protein-energy synchronization (PES) index of the various energy source of feed concentrate in vitro, as a database for the preparation of ruminant rations based on the PES index. The research was conducted from May to August 2020. The research was carried out experimentally through three stages: proximate analysis, in vitro digestibility test, and index calculation. The materials used were rumen fluid of three Jawa Randu Goats, taken shortly after being slaughtered at Sokaraja Goat Slaughterhouse, and seven types of energy sources of feed concentrate. Each feedstuff was duplicated for 3 replications, then the digestibility data for organic matter and protein of each feedstuff were collected at the 2nd, 4th, 6th, 8th, 12th, 24th, and 48th hour by in vitro fermentation. The data collection results were then regressed and the results were included in the PES index equation. The variable measured was the PES synchronization index. The results showed that the PES index of rice bran was 0.54, rice polish 0.50, pollard 0.57, corn 0.87, dried cassava 0.94, dried cassava dreg 0.90, and bread flour 0.94. The study concluded that the energy source of feed concentrate are potential as the medium to the high category of PES index values in the preparation of ruminant rations, where corn, dried cassava, dried cassava dreg, and bread flour have a PES index in the high category, while rice bran, rice polish, and pollard in the medium category. (Indeks sinkronisasi protein-energi berbagai bahan pakan konsentrat sumber energi bagi ruminansia) ABSTRAK. Tujuan penelitian ini adalah menginventarisasi indeks sinkronisasi protein-energi (SPE) berbagai bahan pakan konsentrat sumber energy, sebagai basis data penyusunan ransum ruminansia berbasis indeks SPE secara in vitro. Penelitian dilaksanakan mulai bulan Mei hingga Agustus 2020. Penelitian dilaksanakan secara eksperimental melalui tiga tahap yaitu analisis proksimat, kecernaan in vitro, dan perhitungan indeks. Materi yang digunakan adalah cairan rumen 3 Kambing Jawa Randu yang diambil sesaat setelah disembelih di Rumah Potong Hewan Sokaraja, serta 7 jenis bahan pakan konsentrat sumber energi. Masing-masing bahan pakan diduplikasi sebanyak 3 ulangan, kemudian masing-masing diukur kecernaan bahan organik dan protein pada waktu fermentasi in vitro ke 2, 4, 6, 8, 12, 24 dan 48 jam. Data yang dikoleksi selanjutnya di uji regresi dan hasilnya dimasukkan dalam persamaan indeks SPE. Variabel yang diukur adalah indeks SPE. Hasil penelitian menunjukkan bahwa indeks SPE dedak sebesar 0,54, bekatul 0,50, pollard 0,57, jagung 0,87, gaplek 0,94, onggok kering 0,90 dan tepung roti 0,94. Penelitian menyimpulkan bahwa, konsentrat sumber energi memiliki potensi nilai indeks sinkronisasi protein-energi pada kategori sedang hingga tinggi dalam penyusunan ransum ruminansia. Jagung, gaplek, onggok kering dan tepung roti memiliki indeks sinkronisasi protein-energi pada kategori tinggi, sedangkan dedak, bekatul dan pollard pada kategori sedang.